THE EFFECT OF REPETITIVE KICKING ON KNEE FLEXOR NEUROMUSCULAR FUNCTION. Issue 4 (1st February 2017) - Duhig, Steven; Williams, Morgan; Minett, Geoffrey; Opar, David; Shield, Anthony
Abstract : Background: The primary mechanism for hamstring strain injury is high speed running however insults also occur during kicking in which they are more severe. Objective: To examine the effect of 100 drop punt kicks on isokinetic knee flexor strength and surface electromyographic (sEMG) activity of biceps femoris (BF) and medial hamstrings (MH). Design: Randomised control study. Setting: Community level Australian football. Participants: Thirty-six recreational footballers were recruited. Interventions: Participants were randomly assigned to kicking or control groups. Dynamometry was conducted immediately before and after the kicking or 10 minutes of sitting (control). Main Outcome Measurements: Knee flexor strength and biceps femoris and medial hamstring surface electromyography. Results: Eccentric strength declined more in the kicking than the control group (p<0.001; d =1.60), with greater reductions in eccentric than concentric strength after kicking (p=0.001; d= 0.92). No significant between group differences in concentric strength change were observed (p=0.089; d= 0.60). The decline in normalized eccentric hamstring sEMG (BF and MH combined) was greater in the kicking than the control group (p<0.001; d= 1.78), while changes in concentric hamstring sEMG did not differ between groups (p=0.863; d =0.04). Post-kicking reductions in sEMG were greater in eccentric than concentric actions for both BF (p=0.008; d =0.77) and MH (p<0.001; d =1.11). In contrast, the control group exhibited smaller reductions in eccentric than concentric hamstring sEMG for BF (p=0.026; d =0.64) and MH (p=0.032; d =0.53). Reductions in BF sEMG were correlated with eccentric strength decline (R=0.645; p=0.007). Conclusions: Reductions in knee flexor strength and hamstring sEMG are largely limited to eccentric contractions and this should be considered when planning training loads in Australian Football.